Fifty fifty - Patterson, James, 1947-; Fox, Candice (Patterson, James, 1947- Detective Harriet Blue, 2018)
After violating protocol in her efforts to defend her brother against murder charges, Detective Harriet Blue is reassigned to a small town in the outback, where a diary outlining plans to massacre the entire town is found.